2009
DOI: 10.1002/pmic.200800705
|View full text |Cite
|
Sign up to set email alerts
|

Towards functional proteomics of minority component of honeybee royal jelly: The effect of post‐translational modifications on the antimicrobial activity of apalbumin2

Abstract: This study illustrates multifunctionality of proteins of honeybee royal jelly (RJ) and how their neofunctionalization result from various PTMs of maternal proteins. Major proteins of RJ, designated as apalbumins belong to a protein family consisting of nine members with M(r) of 49-87 kDa and they are accompanied by high number of minority homologs derived from maternal apalbumins. In spite of many data on diversity of apalbumins, the molecular study of their individual minority homologous is still missing. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(63 citation statements)
references
References 34 publications
0
61
0
2
Order By: Relevance
“…An interesting observation was that apa2, the second most abundant protein of RJ did not show antibiotic properties ( Figure 3A, apa2), while the antibiotic activity of its minority homologue, apa2a (apa2a) was significant ( Figure 3B, 5). Apa2a showed in SDS-PAGE a single band of Mw of 48 kDa, which was confirmed by MALDI-TOF-MS (7). The immunochemical analysis confirmed that apa2a is immunoactive to anti-apa2 antibody but Edman sequencing showed that N-terminus of apa2a differed to apa2.…”
Section: Antimicrobial Protein Potential Of Honeymentioning
confidence: 61%
“…An interesting observation was that apa2, the second most abundant protein of RJ did not show antibiotic properties ( Figure 3A, apa2), while the antibiotic activity of its minority homologue, apa2a (apa2a) was significant ( Figure 3B, 5). Apa2a showed in SDS-PAGE a single band of Mw of 48 kDa, which was confirmed by MALDI-TOF-MS (7). The immunochemical analysis confirmed that apa2a is immunoactive to anti-apa2 antibody but Edman sequencing showed that N-terminus of apa2a differed to apa2.…”
Section: Antimicrobial Protein Potential Of Honeymentioning
confidence: 61%
“…Due to its unique valence as health food for humans (as well as its use in health-promoting medical products and cosmetics), the RJ has been the subject of extensive scientific investigations. In the last few years, these studies have been extended to cover its proteome and indeed some selected publications here listed deal with the establishment of the complete RJ proteome [16][17][18][19][20][21]. Perhaps the most extensive report so far is the one of Furusawa et al [19], who have been able to describe a grand total of 52 unique gene products, of which eight belong to the family of the major royal jelly proteins, which are also the most abundant species visible in both SDS-PAGE as well as 2D maps.…”
Section: Discussionmentioning
confidence: 99%
“…Noticeably, the fact that we identified more hemolymph protein spots of MRJP1 in Acc than in Aml may reflect the different PTM status of this protein in the hemolymph of the two bees. It has been reported the glycosylated MRJP2 can effectively inhibit P. larvae infection [35]. Thus it is believed that different bee species may have different adaptive mechanisms of protein modification to meet the nutritional and immune demands for their own larvae.…”
Section: Discussionmentioning
confidence: 99%